Comprehensive Review of the Genetics of Albinism. (November 2018) - Jauregui, Ramon; Huryn, Laryssa A.; Brooks, Brian P.
Introduction: It is important to understand albinism, since it is a disorder associated with visual impairment, predisposition to malignant melanomas, and social stigma. The main objective of this article is to review the genetics and biologic mechanisms of the non-syndromic albinism subtypes and to describe associated clinical manifestations. We also discuss research on its treatments. Methods: A review of the published literature on albinism subtypes was performed, spanning basic laboratory research, published case reports, and experiences of people with albinism. Results: Clear progress has been made in comprehending the causes of albinism; research has shed light on the complexity of the disorder and has led to the molecular classification of subtypes. Discussion: Despite the increase in knowledge with regards to albinism, gaps still exist. It is important to continue the pursuit of unraveling the mechanism of the disorder and to monitor the frequency of the subtypes worldwide in order to aid in the development of treatments. Furthermore, disseminating knowledge of albinism is crucial for future progress. Implications for practitioners: Albinism is a disorder characterized by hypopigmentation of the hair, skin, and eyes, with accompanying ocular abnormalities that remain relatively stable throughout life. The disorder is defined by a spectrum of pigmentation where albinism is more evident among individuals of dark complexion than their lighter-pigmented peers. Patients with albinism require protection against sun exposure and special resources to address visual impairments. When albinism patients are diagnosed and properly accommodated, they generally report a positive quality of life.